2007
DOI: 10.1021/pr0700246
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Detection Methods for Gel-Based Proteomic Analyses

Abstract: Proteomic analyses using two-dimensional gel electrophoresis (2DE) depend heavily upon the quality of protein stains for sensitive detection. Indeed, detection rather than protein resolution is likely a current limiting factor in 2DE. The recent development of fluorescent protein stains has dramatically improved the sensitivity of in-gel protein detection and has enabled more accurate protein quantification. Here, we have evaluated the overall quality and relative cost of five commercially available fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
115
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(120 citation statements)
references
References 39 publications
(90 reference statements)
5
115
0
Order By: Relevance
“…Each silver-stained gel was digitally imaged, and the optical density of each band was determined by investigators masked to rat age and treatment group using computer-assisted image analysis and densitometry (UN-Scan-IT gel version 6.1; Silk Scientific, Orem, UT). The ratio of the density of an individual myosin heavy chain (MHC) band to the total density within a column was used to determine the percentage of each MHC isoform per lane (14,25,27,32,68,76,84). Previous studies have demonstrated good to excellent reliability using these procedures (68).…”
Section: Animalsmentioning
confidence: 99%
“…Each silver-stained gel was digitally imaged, and the optical density of each band was determined by investigators masked to rat age and treatment group using computer-assisted image analysis and densitometry (UN-Scan-IT gel version 6.1; Silk Scientific, Orem, UT). The ratio of the density of an individual myosin heavy chain (MHC) band to the total density within a column was used to determine the percentage of each MHC isoform per lane (14,25,27,32,68,76,84). Previous studies have demonstrated good to excellent reliability using these procedures (68).…”
Section: Animalsmentioning
confidence: 99%
“…Postelectrophoretic protein visualization is most frequently obtained by colorimetric and fluorescent staining methods. The critical factors of staining methods are their sensitivity, reproducibility and the linear range of detection (for a review see [97,98]). Colorimetric methods include CBB and variants, such as Colloidal (C)-CBB or blue silver (C-CBB modified), silver-staining (there are more than 100 variants) and zinc or imidazole-zinc staining.…”
Section: Protein Visualizationmentioning
confidence: 99%
“…Colorimetric methods include CBB and variants, such as Colloidal (C)-CBB or blue silver (C-CBB modified), silver-staining (there are more than 100 variants) and zinc or imidazole-zinc staining. Most of them have linear responses over a very limited range (maximum two orders of magnitude) due to saturation effects that make them unable to cover the great variation in protein concentration of a sample (see discussion reviewed by [97][98][99][100]). CBB-based stainings are simple to use and compatible with MS with a detection limit of around 8-100 ng/spot or 1-100 ng/spot for blue silver [101].…”
Section: Protein Visualizationmentioning
confidence: 99%
See 2 more Smart Citations